2012
DOI: 10.1177/0748233712451773
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short-term treatment with levosimendan on oxidative stress in renal tissues of rats

Abstract: The aim of this study is to evaluate the influences of short-term treatment with levosimendan (chemical formula: C 14 H 12 N 6 O) on oxidative stress and some trace element levels in renal tissues of healthy rats. A total of 20 male Wistar-albino rats were randomly divided into two groups, each consisting of 10 rats. Animals in the first group were not treated with levosimendan and served as control. Animals in the second group were injected intraperitoneally with 12 mg/kg levosimendan and served as levosimend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 18 publications
2
13
0
2
Order By: Relevance
“…Levosimendan has been suggested as a promising agent for protection against oxidative stress [ 1 , 2 ]. Such beneficial effects would involve not only the improvement of hemodynamics, but also direct actions at tissue and cellular levels, which would be related to the mechanisms through which levosimendan could exert its effects.…”
Section: Introductionmentioning
confidence: 99%
“…Levosimendan has been suggested as a promising agent for protection against oxidative stress [ 1 , 2 ]. Such beneficial effects would involve not only the improvement of hemodynamics, but also direct actions at tissue and cellular levels, which would be related to the mechanisms through which levosimendan could exert its effects.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, the significant decrease of SOD, CAT, and GPx activities in the brain and liver point out that alterations in the level of antioxidants, and enzymological activity could be considered the indicators of deteriorating animal homeostasis that further resulted in stress and declined the functional ability (Gecit et al, 2014 andSaravanan et al, 2012). Oxidative insult via deterioration of antioxidant defense capacity is apathogenic pathway involved in all the organ dysfunction or disorders (Saravanan et al, 2012).…”
Section: Discussionmentioning
confidence: 67%
“…In line with that assumption, HNE protein levels (a marker for oxidative stress) were decreased in the diaphragm of levosimendan-treated mice (Figure 2 D). In accordance with the possible ability of levosimendan to reduce oxidative stress, a recent investigation showed that levosimendan treatment increased protective antioxidant enzyme levels in renal tissues of rats [ 41 ]. Myeloperoxidases can induce tyrosine nitrosylation independently of peroxynitrite formation (Figure 5 ) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%